Bone-Derived Factors as Potential Biomarkers for Parkinson’s Disease - Lin, Yuwan; Zhou, Miaomiao; Dai, Wei; Guo, Wenyuan; Qiu, Jiewen; Zhang, Zhiling; Mo, Mingshu; Ding, Liuyan; Ye, Panghai; Wu, Yijuan; Zhu, Xiaoqin; Wu, Zhuohua; et al. (Frontiers in Aging Neuroscience, 2021)
Background: Parkinson’s disease (PD) and osteoporosis are both common aging diseases. It is reported that PD has a close relationship with osteoporosis and bone secretory proteins may be involved in disease progression. Objectives: To detect the bone-derived factors in plasma and cerebrospinal fluid (CSF) of patients with PD and evaluate their correlations with C-reaction protein (CRP) level, motor impairment, and Hoehn-Yahr (HY) stage of the disease. Methods: We included 250 PD patients and 250 controls. Levels of osteocalcin (OCN), osteopontin (OPN), osteoprotegerin (OPG), Sclerostin (SO), Bone morphogenetic protein 2 (BMP2), and Dickkopf-1 (DKK-1) in plasma and CSF were measured by custom protein antibody arrays. Data were analyzed using Mann–Whitney U-test and Spearman’s receptor activator of NF-κB (RANK) correlation. Results: Plasma levels of OCN and OPN were correlated with CRP levels and HY stage and motor impairment of PD. Furthermore, the plasma assessment with CSF detection may enhance their potential prediction on PD. Conclusions: OCN and OPN may serve as potential biomarkers for PD. The inflammation response may be involved in the cross-talk between the two factors and PD.